USING PROJECT TECHNOLOGY IN CHEMISTRY LESSONS - Umarov, Saidanvar (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
In this article, the effectiveness of the use of project technology in chemistry lessons is given. When using project technology in chemistry lessons, students develop general educational skills - the ability to control and evaluate the process and result of activities, to reflect on the methods and conditions of actions. At each stage of work on the project, the formation of personal universal learning activities of students (independent and personal responsibility, readiness and ability for self-development, awareness of responsibility, etc.) takes place.